Synthesis, structures and magnetic properties in 3d-electron-rich isostructural complexes based on chains with sole syn–anti carboxylate bridges. Issue 16 (19th March 2015) - Su, Feng; Lu, Liping; Feng, Sisi; Zhu, Miaoli; Gao, Zengqiang; Dong, Yuhui
Abstract : A series of isostructures based on 2, 2′, 4, 4′-biphenyltetracarboxylic acid have been synthesized via solvothermal reaction, whereas magnetic studies reveal the polymers with sole syn – anti carboxylate bridges show different magnetic behaviors of uniform chains. Abstract : To evaluate magnetic properties of isostructural compounds, a series of 3D carboxylate coordination polymers [M(H2 bpta)] n, (H4 bpta = 2, 2′, 4, 4′-biphenyltetracarboxylic acid, M = Fe(ii ) (1 ), Ni(ii ) (2 ), Cu(ii ) (3 ) and Zn(ii ) (4 )), was synthesized in H2 O–CH3 CN or H2 O solvents, respectively. Structurally, complexes1–4 have isostructural features with (5, 5)-connected 3D framework, wherein the M(ii ) centre takes an octahedral coordination environment consisting of six oxygen atoms from carboxylates of ligands. The M(ii ) sites are linked by syn – anti carboxylates to form chains with an M⋯M separation of 4.880(2) (M = Fe), 4.784(2) (M = Ni), 4.541(2) (M = Cu), and 4.607(2) Å (M = Zn), respectively. The shortest M⋯M distances between interchains locate 9.122(4), 9.077(3), 9.361(3), and 8.767(2) Å, respectively. Magnetically, the isostructural polymers show different magnetic behaviors due to different spins of central ions. Theoretical analysis indicates that couplings between magnetic ions obey uniform chain models. The magnetic susceptibility of1 and2 are perfectly fitted by the modified Fisher model to yield an effective intra-chain exchange coupling constant of −0.81(1) and 3.67(2) cm −1, respectively. For3, a Heisenberg ferromagnetic S = 1/2 chain included the intra-chain magnetic exchange interaction ( J = 9.28(1) cm −1, and zj ′ = −0.068(3) cm −1 ), weak ferromagnetic interactions in intra-chains, and weak antiferromagnetic interactions between interchains. The phenomena of1–3 accord with the common view that the exchange interaction between two magnetic M(ii ) ions bridged by the syn – anti carboxylate bridge is dominantly weak ferro- or anti-ferromagnetic interactions. In addition, the M–O–C–O–M spin exchange interactions |J| of M2 (CO2 )2 (M = Mn(3d 5 ) 20, Fe(3d 6 ), Co(3d 7 ) 20, Ni(3d 8 ), Cu(3d 9 )) decrease in strength with Cu2 (CO2 )2 > Ni2 (CO2 )2 > Co2 (CO2 )2 > Fe2 (CO2 )2 > Mn2 (CO2 )2, consistent with orbit order.